Computational Intelligence Techniques in Diagnosis of Brain Diseases - Gurumoorthy, Sasikumar; Muppalaneni, Naresh Babu.; Gao, Xiao-Zhi.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book highlights a new biomedical signal processing method of extracting a specific underlying signal from possibly noisy multi-channel recordings, and shows that the method is suitable for extracting independent components from the measured electroencephalogram (EEG) signal. The system efficiently extracts memory spindles and is also effective in Alzheimer seizures. Current developments in computer hardware and signal processing have made it possible for EEG signals or "brain waves" to communicate between humans and computers - an area that can be extended for use in this domain.
1.Introduction -- 2.Analysis of Electroencephalogram (EEG) using ANN -- 3.Classification and Analysis of EEG using SVM and MRE -- 4.Intelligent Technique to Identify Epilepsy Captures Using Fuzzy System -- 5.Analysis of EEG to find Alzheimer's disease using Intelligent Techniques.
Keywords: Computational intelligence; Neurology .; Biomedical engineering; Signal processing; Bioinformatics; User interfaces (Computer systems).; Human-computer interaction; Computational Intelligence; Neurology; Biomedical Engineering and Bioengineering; Signal, Speech and Image Processing; Computational and Systems Biology; User Interfaces and Human Computer Interaction